Paronychia revoluta, a new species of caryophyllaceae from Brazil - Carneiro, O. E.; Furlan, A. (Missouri Botanical Garden, 2004)
A new species of Paronychia, P revollita, from the state of Rio Grande do Sul, Brazil, is described and illustrated. This species is closely related to P camphorosmoides, distinguished from it by linear-subulate leaves with a revolute margin and prominent midribs. It is also allied to P. fascicidata, from which it differs in the lanceolate, acuminate, fimbriate, and whitish stipules, and linear-subulate leaves.
Keywords: Brazil; caryophyllaceae; Paronychia